2013
DOI: 10.1155/2013/143047
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Sequential with Triple Therapy forHelicobacter pyloriin an Aboriginal Community in the Canadian North

Abstract: While additional evidence is needed to confirm that ST is more effective for Arctic Aboriginal communities than the Canadian standard H pylori treatment, these results show standard PPI-CA treatment to be inadequate for communities such as Aklavik.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…High treatment failure rates have been demonstrated elsewhere in the Arctic; Johansen et al reported that 68% of subjects treated with a metronidazole‐based regimen failed the first treatment . Morse et al performed a study that demonstrated high treatment failure rates for clarithromycin‐based standard triple therapy (41%) and clarithromycin‐based sequential therapy (27%) in the northern Northwest Territories of Canada …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…High treatment failure rates have been demonstrated elsewhere in the Arctic; Johansen et al reported that 68% of subjects treated with a metronidazole‐based regimen failed the first treatment . Morse et al performed a study that demonstrated high treatment failure rates for clarithromycin‐based standard triple therapy (41%) and clarithromycin‐based sequential therapy (27%) in the northern Northwest Territories of Canada …”
Section: Discussionsupporting
confidence: 92%
“…38 Morse et al performed a study that demonstrated high treatment failure rates for clarithromycin-based standard triple therapy (41%) and clarithromycin-based sequential therapy (27%) in the northern Northwest Territories of Canada. 39 In this study, we documented no change in symptoms post-treatment among patients successfully treated vs those unsuccessfully treated except for stomach pain which appeared to improve posttreatment. These findings are consistent with other studies around the world that demonstrate this lack of symptom resolution posttreatment 40 ; however, there are many other studies with conflicting results, showing a resolution of symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…For instance, the Canadian guidelines recommend against sequential therapy, although only one study was performed in that country [58]. Specifically, a total of 104 patients from Arctic aboriginal community were enrolled, with 51 cases in the sequential therapy and 49 in the triple therapy arm, showing disappointing results for both therapies.…”
Section: Bismuth-free Therapiesmentioning
confidence: 99%
“…Thus, there is a need to identify effective H pylori eradication regimens in this at-risk population. In the current issue of the Journal, Morse et al (2) (pages 701-706) report results from a randomized controlled trial comparing sequential versus standard clarithromycin-containing triple therapy in H pylori-infected adults from the community of Aklavik (Northwest Territories) (2). The study was part of a participatory research project focusing on community-identified research goals investigating the burden of H pylori disease in Arctic Aboriginal communities.…”
Section: Anadian Aboriginal Populations Have a High Prevalence Ofmentioning
confidence: 99%
“…In the study by Morse et al (2), H pylori-infected patients >15 years of age were randomly assigned to either a 10-day treatment of standard triple therapy consisting of a proton pump inhibitor (rabeprazole), amoxillicin and clarithromycin, or sequential therapy. Antibiotic resistance rates to clarithromycin and metronidazole were available for almost one-half of the subjects, allowing tailored treatment.…”
Section: Anadian Aboriginal Populations Have a High Prevalence Ofmentioning
confidence: 99%